CRITICAL ANALYSIS: THE IMPACT OF LABORATORIES ON PANDEMIC MANAGEMENT - Mohammed Hamad Alzibarah, Mohammed Ibrahim AL Sagoor, Mohammed Hamad Al Mansour, Hadi Mohammad Almnsoore, Ayed Mesfer Al-Sleem, Mohammed Saleh Ali Al Sulaiman (Chelonian Research Foundation, 2023)
This article presents a critical analysis of the role laboratories have played in managing pandemics, highlighting their indispensable contributions to disease detection, surveillance, research, and vaccine development. Through a comprehensive review, we explore the multifaceted challenges laboratories face, including resource constraints, testing capacity issues, and the need for rapid, accurate responses. Technological advancements in laboratory science, such as high-throughput sequencing and bioinformatics, have significantly bolstered pandemic management, yet they also raise complex ethical and logistical questions. The paper emphasizes the critical importance of international collaboration in enhancing laboratory responses, sharing data, and resources to combat global health threats. We further delve into the impact of government policies and infrastructure on laboratory effectiveness, proposing policy improvements based on lessons learned from recent pandemics. The analysis concludes by discussing emerging trends and the necessity of preparedness to improve future responses. This study aims to provide valuable insights into the strengths and limitations of current laboratory practices in pandemic management and suggests avenues for future research and policy development. Keywords: Pandemic Management, Laboratory Science, Disease Detection, Technological Advancements, International Collaboration, Ethical Considerations, Public Health Policy, Future Preparedness